Management of biodegradable plant tissue culture lab wastes through biomethanogenesis - Abdulla Fayas T (Centre For Plant Biotechnology and Molecular Biology, College of Horticulture, 2008)
Generating renewable source of energy from tissue culture laboratory waste by the process of biomethanogenesis is the focal theme of present investigation. Unlike developed countries, the developing countries are hesitant to establish more number of biotechnology/ tissue culture laboratories due to financial constraints. Easy and regular availability of biogas from TC wastes will be a boon to establish self-sustainable TC laboratory in view of present energy The biogas experimental units required for the study was designed and various treatments were employed for the biodegradation of tissue culture waste, using the methanogenic bacteria Methanobacterium ruminatium, Methanobacterium formicicum; Methanosarcina barkeri, Bactereoides ruminicola, Selenomonas ruminatium, Eubacterium tortuosum and Clostridium butyricum. Treatment involving TC waste and cow dung was also conducted for biomethanation in the present study. Quantity of gas production and its combustibility was noticed for various treatments. In bacterial treatments the quantity of gas generation was highest for Clostridium butyricum. Only treatments involving cow dung produced combustible gas. Molecular characterization, of methanogenic bacterial cultures was also done for finding the genetic similarity between them. RAPD followed by scoring . of the bands by UPGA routine showed maximum similarity between bacterial cultures of Methanobacterium ruminatium and Methanobacterium jormicicum with Methanosarcina barkeri. Physio-chemical characters like CIN ratio of the TC wastes, pH and temperature of medium and Hydraulic retention time was also observed for the various treatments. The CIN ratio of the TC wastes was found to be very low and nowhere near the optimum CIN ratio of 20-30 required for gas production. Other parameters like pH of the treatments and Hydraulic retention time was also.